Phytoextraction of Heavy Metals from the Soil of Aurora-Patricia Mining Environmental Liability by Herbaceous Species Carex mandoniana, Equisetum bogotense, and Muehlenbeckia tamnifolia, La Encañada-Peru 2020. - López Rodríguez, C.C. (2021)
The Cajamarca region has a large number of mining environmental liabilities; one of them is the former mining company Aurora - Patricia, which operated in the small town of Polloc. Since 1985 its operations have been stopped. Based on this, we determined the phytoextraction capacity of 13 heavy metals in three herbaceous species that grow in this place with the highest rate of importance value. To do this, we applied the stratified random sampling and square meter methods, where it was possible to identify 42 herbaceous species in 10 plots, of which Equisetum bogotense, Muehlenbeckia tamnifolia and Carex mandoniana were chosen. The concentration of heavy metals was analyzed from both contaminated (environmental liability) and non-contaminated (around the liability) soils of La Encañada district, as well as in herbaceous species to compare them. The highest correlation between variables was obtained from Carex mandoniana species (0.995), followed by Equisetum bogotense (0.975) and, on the other hand, Muehlenbeckia tamnifolia presented a negative inverse relationship. The Bioconcentration Factor was calculated where it turned out that the herbaceous species are exclusive; however, the Translocation Factor showed that Equisetum bogotense and Carex mandoniana are phyto-stabilizers while Muehlenbeckia tamnifolia is hyper-accumulative of heavy metals.